KEABSAHAN PERJANJIAN DAN KEDUDUKAN PINJAMAN ONLINE ILLEGAL SEBAGAI KREDITUR DALAM KEPAILITAN - Nicholas, Jason (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
Online loans in Indonesia are becoming a growing business. Every day there are more and more online loans, some of which are even illegal.This scientific article was written to examine the bankruptcy that can be occurred in online loan debtors. The purpose of this article is to provide answers to what can be done when an illegal online loan debtor goes bankrupt. because online loans are a type of debt, they can be a reason for bankruptcy. Therefore, this research is expected to help bankrupt debtors if they are caught in illegal loans. The research was conducted normatively using books, journal articles, and articles in online media as research sources. Using the sources, researcher make facts based on the writings. The study concluded that illegal online loan agreements are valid in the eyes of the law until the agreement is terminated by a judge.